Difference-making factors for successful implementation of a multicomponent colorectal cancer screening program in rural clinics (SMARTER CRC) - Amanda F. Petrik; Brittany Badicke; Melinda M. Davis; Melinda M. Davis; Melinda M. Davis; Edward J. Miech; Jennifer Coury; Erin S. Kenzie; Erin S. Kenzie; Jennifer L. Schneider; Robert Durr; Anna C. Edelmann; et al. (Frontiers in Medicine)
IntroductionRural disparities in colorectal cancer (CRC) screening persist despite the availability of effective, evidence-based interventions. In this study, we aimed to understand what characteristics lead to success when implementing a multicomponent CRC screening intervention in rural primary care clinics in a pragmatic clinical trial (SMARTER CRC).MethodsWe applied coincidence analysis to identify solution pathways that led to successful implementation during the first year of SMARTER CRC in intervention clinics. We assessed clinic success as high/low rates of fecal immunochemical testing (FIT) and overall CRC screening. Factors included in the analysis were collected through qualitative interviews, practice facilitation notes, and project datasets.ResultsA total of 14 intervention clinics were included in our analysis. Post-intervention, overall clinic-level screening rates for CRC ranged from 12.6 to 22.0%, while FIT completion rates among patients who were mailed a kit ranged from 12.3 to 41.7%. Values for three factors perfectly distinguished between clinics with higher and lower CRC screening rates: clinics sending a pre-FIT introduction letter on their own, clinics having prior (or current) experience with CRC screening campaigns, and clinics changing the type of FIT they used. For FIT screening rates, two factors perfectly distinguished between clinics with higher and lower rates: clinics sending introduction letters on their own and clinic staff attending four or more health plan/clinic meetings.DiscussionHigher FIT and CRC screening rates were associated with clinics that were able to mail an introductory letter, had experience in CRC screening campaigns, did not change their FIT, and attended the health plan/clinic meetings. These clinic-level factors appear to be difference-makers to the successful implementation of a CRC screening program in rural settings.